APOE and CLU cooperatively promote amyloid formation. (20th December 2022) - Ding, Zonghui; Haug, Katelin; Fryer, John D.
Abstract: Background: Apolipoprotein E (APOE) and clusterin (CLU) are critical in the pathogenesis of Alzheimer's disease (AD). Common coding variants in APOE (e.g. APOE4) impart at least 3‐fold higher risk of developing AD, while common noncoding variants in CLU impart smaller but still highly significant risk for AD. Using genetically engineered mouse models lacking either APOE or CLU, previous studies from our lab and others have shown that both are critical in the formation of amyloid. However, only a single published study has examined the combined effects of APOE and CLU in a mouse model of amyloidosis. Methods: We generated mice that lacked both murine APOE and CLU (double knockout mice) on the APP/PS1 background of AD amyloidosis. We assessed these mice using histological analysis as well as single‐cell RNAseq profiling from brain tissue. Results: Compared to APP/PS1 controls, we found that double knockout mice for both APOE and CLU had a striking reduction in the amount of amyloid plaques in the cortex. Moreover, we found that these double‐knockout mice were completely void of amyloid plaques in the hippocampus. Single‐cell RNAseq experiments revealed a strong reduction in the amount of activated microglia in these double knockout mice. Conclusions: Contrary to a previous study that reported increased amyloid load in APOE‐/‐;CLU‐/‐ double knockout mice, we found a dramatic reduction in amyloid plaques and a concomitant loss of activated microglia when using genetically inbred (C57BL/6J) mouse lines. Further studies are needed to determine whether these effects are cell‐type specific (e.g. astrocyte‐derived APOE and CLU conditional knockouts) or whether these lipoproteins have synergistic roles in tau pathology.